Особливості функціонування спортивних термінів у засобах масової інформації - Карпець, Д. С. (ХНУРЕ, 2022)
The article deals with topical problems of the development of sports terminology and its demonstration in the media for many years. It is clarified what period the appearance of sports nomen belongs to. The role of the media in promoting the penetration of sports nomen to wide social networks, which form a specific microsystem of the Ukrainian language, is outlined. The article clarifies the historical aspects of formation of sports terminology as a social phenomenon. Author points out the intensive enrichment of the Ukrainian language with the names of new kinds sports or the names of sports that have not been practiced.